The Relationship Between Brain Tumor And Sleep Components (Psqi) In Siloam Hospitals Lippo Village 2015-2018 - Uranus, Hans Christian; July, Julius (Medicinus, 2019)
Introduction: Brain tumor can cause symptoms such as headache and seizure which might reduce sleep quality. Currently, sleep quality in brain tumor patients aren’t getting much attention. This study’s purpose is to determine the effect of brain tumor to sleep quality and its components in patients.Methods: The design of this study is a retrospective cohort, and it is done in Siloam Hospitals Lippo Village and Paviliun Umum Rumah Sakit Siloam from January-April 2019 with sample population consisting of brain tumor patients from age 19 until 59 years old. The sample amount is 29 subjects. PSQI is used to assess sleep quality and components. Data analysis uses the SPSS version 24.0 software and statistical  analysis using chi2.Result: Brain tumor patients have worse sleep quality compared to the control, with 26 patients (89.7 %) having bad sleep quality. For the control, there are only 18 people (62.1%) who have bad sleep quality. The relationship between brain tumor and sleep quality have a p value of 0.032 and relative risk (RR) of 3,7. Brain tumor has a significant relationship with sleep latency (p value 0,015) and daytime dysfunction (p value 0,02)Conclusion: The relationship between brain tumor and sleep quality in brain tumor patients of Siloam Hospitals Lippo Village and Paviliun Umum Rumah Sakit Siloam, which was measured with the PSQI questionnaire is significant. Brain tumor also has a significant relation with sleep latency and daily dysfunction.